ALISKIREN (RENIN INHIBITOR) AS THE RECENT ANTIHYPERTENSIVE MODALITY - Suaka Putri, Luh Gde Primahatini (E-Jurnal Medika Udayana; vol 2 no 12 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Hypertension is a chronic disease which is commonly found. Many people pay attention on it. The prevalence of hypertension all over the world is almost one billion , of which mortality is approximately 1,7 million each year . The renin - angiotensin - aldosterone system ( RAAS) has an important role which caused hypertension . T wo kind of drugs which work on RAAS and recently used widely are angiotensin - converting enzyme inhibitors ( ACEI) and angiotensin receptor blocker ( ARB). Both of them have weakness in blocking RAAS and their side effects. Renin is an important component in RAAS and has specificity for angiotensinogen . Renin inhibitors can block RAAS at the highest level. Aliskiren is the first renin inhibitor which can be oral ly given and has developed until the clinical trial of the third phase . The disadvantages of ACEI and ARB can be solved because of the aliskiren. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: aliskiren, renin inhibitor, hypertension